2023
DOI: 10.1161/jaha.123.030834
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bypass Surgery and Mortality in Moyamoya Disease

Hyunjun Park,
Minkyung Han,
Dong‐Kyu Jang
et al.

Abstract: Background Patients with moyamoya disease (MMD) have a high risk of stroke or death. We investigated whether extracranial to intracranial bypass surgery can reduce mortality by preventing strokes in patients with MMD. Methods and Results This nationwide retrospective cohort study encompassed patients with MMD registered under the Rare Intractable Diseases program via the Relieved Co‐Payment Policy between 2006 and 2019, using the Korean N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Despite this, the lack of speci c data on MMD-related stroke risks underscores the need for further research to clarify this potential risk factor. Moreover, our research indicates that RS signi cantly reduces the risk of stroke-related events (OR 0.38 [95% CI 0.21-0.70]) and mortality (OR 0.41 [95% CI 0.24-0.89]), as numerous studies have demonstrated that RS is bene cial in preventing strokes in patients with MMD [37][38][39] . These ndings suggest that maintaining a normal BMI and considering RS as a preventive measure against further stroke, irrespective of COVID-19 considerations.…”
Section: Modi Able Risk Factors For Stroke In MMD Patientsmentioning
confidence: 78%
“…Despite this, the lack of speci c data on MMD-related stroke risks underscores the need for further research to clarify this potential risk factor. Moreover, our research indicates that RS signi cantly reduces the risk of stroke-related events (OR 0.38 [95% CI 0.21-0.70]) and mortality (OR 0.41 [95% CI 0.24-0.89]), as numerous studies have demonstrated that RS is bene cial in preventing strokes in patients with MMD [37][38][39] . These ndings suggest that maintaining a normal BMI and considering RS as a preventive measure against further stroke, irrespective of COVID-19 considerations.…”
Section: Modi Able Risk Factors For Stroke In MMD Patientsmentioning
confidence: 78%